Method for simultaneous quantification of veterinary antibiotics and hormones in soil and biosolids - Zakaria, Mohamad Pauzi; Ho, Yu Bin; Abdul Latif, Puziah; Saari, Nazamid (2012)
A new method is developed to determine veterinary antibiotics and hormone in solid environmental samples by high performance liquid chromatography combined with tandem mass spectrometry (HPLC-MS/MS) using isotope dilution and internal standard quantitation techniques. This method has been developed particularly for simultaneous determination and quantification of nine antibiotics (doxycycline, erythromycin, enrofloxacin, flumequine, norfloxacin, sulfadizine, tilmicosin, trimethoprim and tylosin) and one hormone (progesterone) in animal manure, soil, and compost matrices. The developed method is based on solid phase extraction (SPE) followed by instrumental analysis using liquid chromatography electrospray ionization-tandem mass spectrometry (LC–ESI-MS/MS) with 25 minutes total run time.